The Rohingya Diaspora: A Narrative Inquiry into Identity - Fazal, Muhammed Bilal; Lee, Kean Wah (Journal of Ethnic and Cultural Studies, 2023)
This study examined the key experiences and aspects of the life of Rohingya diaspora youth through exploratory Narrative Inquiry. Three semi-structured interviews were held with six participants from the Rohingya community in Malaysia. Responses were analyzed and categorized into three broad sections based on Cultural Historical Activity Theory: environmental impacts on lived experience, the diversity of sociocultural origin within the Rohingya community, and the impact of historical processes on cultural change. It was noted that the Rohingya culture is rich with diverse experiences and origins far beyond its current circumstances. Rohingya youth identify strongly with their experiences of life in Arakan and note that the younger generations missing this experience are less connected with their Rohingya identity. Beyond that, much of the threat to self-perception within the community came from external reductive narratives based only on their plight. In order to establish a constructive framework to support the Rohingya people, it is therefore critical to better understand them as a culture beyond their hardships.